METHOD OF PAYMENT AND ACQUIRER SHAREHOLDER WEALTH MAXIMIZATION IN MERGERS AND ACQUISITIONS: A REVIEW OF LITERATURE - Jagan Arumugam; Rubi Ahmad; Koh Hsieng Yang (The International Journal of Banking and Finance)
This paper aims to review existing literature to study the relationship between the method of payment and the acquirer firm’s shareholder wealth in mergers and acquisitions (M&A). The literature review is carried out in two areas: (1) payment methods offered to the target firm based on the acquirer firm’s internal factors, and (2) the impact of different payment methods on shareholder wealth during the announcement period. The paper is focused on providing suggestions for future studies on the payment methods, specifically on the mixed payment method. This paper is the first attempt to critique extant literature, beginning with selecting the payment method and ending with how it would affect the acquirer firm’s shareholder wealth. Since this is a review paper and not subject to empirical study, it could be directed for future research to investigate the impact of the cash-to-stock ratio in the mixed method of payment offer on the wealth of the shareholders of the acquirer firm.